(untitled) (Lundiana: International Journal of Biodiversity, 2011)
Chironomid larvae are frequently found living in phoretic or commensal association with aquatic animals in all regions of the world. In Brazil, new records have been available in the literature in the last years mainly for the state of São Paulo. In collects performed in several streams and rivers in the state of Rio de Janeiro and bordering areas, chironomid larvae were found living in association with Corydalidae (Megaloptera); Perlidae (Plecoptera); Leptophlebiidae (Ephemeroptera); Aeshnidae and Libellulidae (Odonata); Sericostomatidae (Trichoptera); Elmidae (Coleoptera) and catfishes of the families Trichomicteridae and Loricariidae (Pisces). These new records are presented in the present study.